Caracterização da pecuária leiteira do município de Muriaé, MG: uma reflexão sobre perspectivas futuras - Vasconcelos, João Marcos Carvalho (2017)
The objective of this work is to evaluate the current situation of the activity, production base and technological level used by the producers affiliated to the Muriaé Livestock Program, in the following points: characteristics of the properties, productivity, animal nutrition, techniques developed and animal health. The work includes a micro-region of the municipality of Muriaé / MG, 129 producers affiliated to the Muriaé Livestock Program were interviewed, with a semi-structured questionnaire application. The questionnaire included: characteristics of the properties, productive activities, animal nutrition, techniques developed and animal health. Small farms, consumer goods, leased and lending station, main income dairy production, household base labor in most of the properties, non-agricultural activities in the part of the dynamics of the properties, Variation of five species of grasses, breeds European cattle, and the cross between them. The productive process in the properties and directed to the milk production, as well as a herd aptitude, with media production of 113 liters, commercialization in laboratory, cooperative, fair free and informal commerce. Animal nutrition computes in fourteen different food management. The animals of the properties are in the preventive program of diseases and diseases, result obtained by veterinary interaction carried out by the program, as well as the conventional management. A livestock activity of the family producers of Muriaé is with low specialization, its base production is the production of milk, followed by secondary activities without increase of income, as the properties are with the technological deficiency in the use of the maximization of production of milk.